From Known Unknowns to Black Swans : How to Manage Risk in Latin America and the Caribbean - Vegh, Carlos A. (Washington, DC: World Bank, 2018)
After a growth recovery, with an expansion of 1.1 percent in 2017, the region has encountered some bumps in the road. The Latin America and the Caribbean (LAC) region is expected to grow at a modest rate of 0.6 percent in 2018 and 1.6 percent in 2019. This slowdown in the region’s recovery is mainly explained by the crisis that started in Argentina in April, the growth slowdown in Brazil, and the continuing economic, social, and humanitarian collapse in Venezuela. Furthermore, net capital inflows to the region have fallen dramatically since early 2018, bringing once again to the fore the risks faced by LAC. In addition, natural disasters such as earthquakes and hurricanes have brought devastation to the region with disturbing frequency. The core of the report analyzes the foundations of risk, develops a theoretical framework to price risk instruments, and reviews how LAC has managed risk in practice. The overall message of the report is that there are different types of risk: (i) those that follow standard probabilistic distributions that can be easily insured by the market; and (ii) those that exhibit fat-tails (i.e., non-negligible probabilities of extreme events) that are much harder to ensure by the market (like earthquakes). Finally, there are “black swans” that, by definition, are unpredictable events that cannot be insured and force countries to rely exclusively on ex-post aid and/or broad preventive measures. In other words, the fatter are the tails of a distribution, the less market insurance is available, and the more countries will have to rely on ex-post aid. Yet progress in managing risk continues to be made (the Catastrophe Bond for earthquakes in the Pacific Alliance, recently sponsored by the World Bank, being an outstanding example). This would have been unthinkable some time ago. New knowledge and insurance schemes, all supported by institutions such as the World Bank, will undoubtedly make LAC a safer region to live and prosper.